Stylistic of The Qur’an: The Existence of Majaz Mursal I’tibar Ma Kana - Murdiono, Murdiono; Fatoni, Ahmad; Sarimov, Renat (Universitas Islam Negeri Raden Intan Lampung, 2021)
The existence of majaz mursal i'tibar ma kana in the Qur'an has proven the use of majaz style of language in the Qur'an which underlined that the Qur’an cannot be separated from majaz. The study of the Qur'an will cause the ambiguity in meaning and even fatal mistakes if balaghah approach (majaz) is not used. The data of this research were obtained from the Qur'an and the opinions of several Balaghah experts, such as Abu Ubaidah and Az-Zamakhsyary as the source of information in this study. Semantics was also used in this research, which was analyzing the meaning of the verses of the Qur'an which were classified as majaz i'tibar ma kana. The research results showed that there were 12 verses in the Qur'an including majaz mursal i'tibar ma kana which were found in the different verses, such as surah Al-Baqarah verse (2): 234, surah An-nisa verse (4): 2, surah An-nisa verse (4) 12, surah Al-Rahman verse (55): 56, surah Al-Kahfi verse (28): 47, surah Al-Hujarat verse (49): 9, surah: An-Naml verse (27): 87, surah Fussilat verse (41): 21, surah Thaha verse (20): 74, surah Nuh verse (71): 26-2, surah Ad-Dhukhan (44) verse: 47,48 49. So, there must be a meaningful figure of speech (metaphor) in understanding the verses of the Qur'an and there was no ambiguous meaning. Therefore, this study suggested the need to explore the science of balaghah as one of the tools of science in understanding the Qur'an implicitly.